Analysis of Product Quality, Locations and Services of Culinary SMEs In Restaurants Toward Customer Loyalty: A Study of Customer Satisfaction In Pandemic Times - Zamiah Hasibuan; Sumitro Sarkum; Mulya Rafika (Quantitative Economics and Management Studies, 2022)
This study aims to analyze the quality of products, locations and services of SMEs _ partially and partially on customer loyalty in Labuhanbatu during the pandemic. The research methodology used is quantitative, with a population of 8,130, a sample of 381 respondents, with a probability sampling technique using simple random sampling. The data collection technique used SPSS varsi 20. The instrument test used validity and reliability tests. The pandemic has had an impact on various aspects of society, especially SMEs. There are impacts that arise during the pandemic such as aspects of sales, aspects of business profits, aspects of capital and aspects of the ability of all culinary business actors to experience these problems due to the pandemic period. Culinary businesses apply online sales strategies, although not all of them. The community buying electricity during the pandemic caused a lot of loss of income so that people buying electricity were reduced due to the pandemic period, the situation of the community when they made purchases using the online method and were active at home. Interview results show that there is a pandemic for SMEs. Where is the impact of culinary businesses such as uas players who experience a decrease in the level of people's purchasing power because they reduce their activities outside the home community. There is an attempt by actors to increase their business opinion in the midst of the Century pandemic by learning about technology, providing good service and maintaining the quality of the products to be sold to consumers. The results of this study conclude that partially and simultaneously there is a significant and positive effect between product quality, location, service on customer satisfaction and loyalty and there is a significant and positive influence between satisfaction and customer loyalty.